Uji Ekstrak Bawang Bombay sebagai Anti Bakteri Gram Positif Staphylococcus aureus dengan Metode Difusi Cakram - Wuryanti, Wuryanti; Mulyani, Nies Suci; Asy'ari, Mukhammad; Sarjono, Purbowatiningrum Ria (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2010)
Microbe is a microscopic living organism which is closely linked to human life. One of pathogenic microorganisms such as Staphylococcus aureu,. may cause diseases. Sulfure of several plants are bioactive as antimicrobial. The properties of sulfure in Allium cepa L leads to an assumption that it has antimicrobial properties. Therefore, this study involved the antimicrobial test. The determination steps of antimicrobial Allium cepa L extract consisted of the Allium cepa L extract preparation, microbial regeneration and antimicrobial test. The antibacterial determination were performed by paper disc method. Based on the research data, determination of antimicrobial Allium cepa L extract resulted in inhibition zone area showed that the extract owned antimicrobial property.